A study on occupational aspirations of senior secondary school students of a selected school of Mandi district, Himachal Pradesh - Chauhan, Urmila; Sharma, Nidhi; Kaur, Jaswinder (International Journal Of Community Medicine And Public Health, 2024)
Background: Life is full of struggles and an individual has to face numerous challenging situations where there is need to make right decisions. In the era of advancement of scientific knowledge and gradual development of materialistic outlook, it is believed that education should enable the individual to earn his living. Occupational aspirations in the early years of life influence the vocational choice in the later life, which determine individual’s success in regard to job satisfaction, productivity and adjustment. Hence this study was undertaken with a view to make an attempt to study the occupational aspirations of senior secondary school students of Mandi district. Methods: Descriptive cross-sectional survey method was used. A sample of 100 students (50 girls and 50 boys) of senior secondary level (classes XI and XII) was randomly selected from the selected Government senior secondary school. Occupational aspiration scale by Dr. J. S. Grewal was used to collect data for the study. For data analysis, percentage, mean, standard deviation and t-test were used. Results: Majority, i.e., 76% senior secondary students were found to have average occupational aspiration level. No significant difference was found in occupational aspiration level between urban and rural senior secondary students. Conclusions: Majority of senior secondary students were found to have average occupational aspiration level, thus highlighting the importance of guiding the students from secondary education stage towards selection of a right career according to their occupational aspirations.